Involvement of MEK-ERK1-2 pathway in the anti-oxidant response in C6 glioma cells after diesel exhaust particles exposure. (27th May 2016) - Farina, Francesca; Milani, Chiara; Botto, Laura; Lonati, Elena; Bulbarelli, Alessandra; Palestini, Paola
Highlights: DEP induces oxidative stress in C6glioma cells. C6glioma cells have an anti-oxidant strategy in order to regulate oxidative stress. The anti-oxidant strategy relies on the activation of MEK-ERK-1-2 pathway. Abstract: Ultrafine particles translocate to the central nervous system and activate oxidative stress-related pathways. The transcription factor Nrf2 activation by ERK1-2 has been suggested as a key regulator of cellular response to oxidative stress. C6 glioma cells have been treated with different doses of diesel exhaust particles (25 μg/ml, DEP25, and 50 μg/ml, DEP50), for different times. Cells have been screened for oxidative stress and inflammatory markers, and for the activation of the MEK-ERK1-2 pathway. The same markers have been examined after inhibition of MEK, the kinase upstream to ERK1-2. 3 h and 24 h of DEP25 and DEP50 induced a significant increase in HO-1 levels. After 24 h, DEP25 and DEP50 induced an increase in HO-1 and Cyp1b1 levels, while increase in OGG1 level was observed only with DEP25. After 5 h of treatment with DEP25, ERK1-2 resulted phosphorylated, concomitantly with a significant increase in HO-1 levels, no changes in iNOS levels, and decreased levels of anti-oxidant enzymes. After treatment with MEK inhibitor U0126, ERK1-2 showed no activation, with a consequent decrease in Nrf2, no increase in HO-1 and a significant increase of iNOS. MEK inhibitor is able to deplete anti-oxidant enzymes. In conclusion, the MEK-ERK1-2 pathway is involved in regulating the anti-oxidant strategies to compensate the oxidative status induced by DEP treatment.